Stock risk and return before and during the covid-19 pandemic - Alther Gabriel Liwe (Yayasan Widyantara Nawasena Raharja, 2023)
Based on the type of data used, this research uses a quantitative approach, which places an emphasis on testing theory through measuring research variables with numbers and conducting data analysis with statistical procedures. One of the models used to estimate the rate of return is the Capital Asset Pricing Model (CAPM). The purpose of this study is to examine the level of risk and stock returns during the covid-19 pandemic using the Capital Asset Pricing Model (CAPM) method in companies listed on the Indonesia Stock Exchange (IDX) and to examine differences in the level of risk and stock returns before and during the covid-19 pandemic in companies listed on the Indonesia Stock Exchange. Determination of the sample using the purposive sampling method. There are 488 companies on the Indonesia Stock Exchange (IDX) that meet the criteria, with 98 companies classified as high-risk companies and 390 companies classified as low risk. The results showed that there were no significant differences in risk and stock returns in high-risk companies before and during the pandemic in 2020, 2021, and 2022. There is a significant difference in risk and stock returns in low-risk companies before and during the pandemic in 2021, while there is no significant difference before and during the pandemic in 2020 and 2022. There is a significant difference in risk and stock returns in high- and low-risk companies before and during the 2021 pandemic, while there is no significant difference before and during the 2020 and 2022 pandemics.